2016
DOI: 10.1039/c5nr04366b
|View full text |Cite
|
Sign up to set email alerts
|

Layer-dependent surface potential of phosphorene and anisotropic/layer-dependent charge transfer in phosphorene–gold hybrid systems

Abstract: We investigate the anisotropic hybrid plasmon-SO phonon dispersion relations in monolayer and double-layer phosphorene systems located on the polar substrates, such as SiO2, h-BN and Al2O3. We calculate these hybrid modes with using the dynamical dielectric function in the RPA by considering the electron-electron interaction and long-range electric field generated by the substrate SO phonons via Fröhlich interaction. In the long-wavelength limit, we obtain some analytical expressions for the hybrid plasmon-SO … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
70
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 65 publications
(72 citation statements)
references
References 35 publications
2
70
0
Order By: Relevance
“…Other works are categorized toward environmental engineering modulations in the external environment within the vicinity of 2D layers, such as dielectric screening, chemical doping, magnetic field, and substrates . Environmental dielectrics have been found to strongly influence the Coulomb interactions in low dimensional materials .…”
Section: Modulation Of Materials Propertiesmentioning
confidence: 99%
“…Other works are categorized toward environmental engineering modulations in the external environment within the vicinity of 2D layers, such as dielectric screening, chemical doping, magnetic field, and substrates . Environmental dielectrics have been found to strongly influence the Coulomb interactions in low dimensional materials .…”
Section: Modulation Of Materials Propertiesmentioning
confidence: 99%
“…But no detailed experimental or theoretical studies have been directed toward in‐plane isotropic/anisotropic until this date. However, Xu et al investigated the anisotropic PL quenching of BP in a BP–Au structure, this quenching was due to possible band alignments in between the gold (Au) and BP . Figure presents the Au–BP hybrid system with anisotropic PL emissions from BP and its anisotropic PL quenching in an Au–BP hybrid system.…”
Section: Unique 1d/2d Quasiparticles Dynamics Of In‐plane Isotropic/amentioning
confidence: 99%
“…TheSKPM images show that the WF of the BP flakes ranges from 4.45 to 4.75 eV.P ristine (0 hour) BP shows alayer-dependent WF as previously reported. [25,26] Combined with AFM topography,itwas shown that the time evolution of the WF also depends on the number of layers even under dark conditions.T ou nderstand the time evolution of the layerdependent degradation, topographical and chemical changes on the BP surface are discussed below. Figure 2s hows the time-dependent height profiles obtained from the dotted arrows (profile A) in Figure 1a across 2L (blue) and bulk BP (red) over 48 hours.The inset of Figure 2shows that the height of the 2L region had gradually increased by 2.5 nm after 6hours (or 15 hours in an average manner throughout the whole 2L region, see Figure 3below), and then bubbles began to form.…”
mentioning
confidence: 99%